Determinantes da eficiência técnica e econômica da citricultura em propriedades rurais do Estado de São Paulo - Carrer, Marcelo José (2015)
The aim of this study was to measure the technical and economic efficiency differentials in citrus production among farms in the State of São Paulo, Brazil, as well as to identify the determining factors of these differentials. In addition, it was also an objective to investigate the main characteristics of citrus production technology (partial elasticities, returns of scale, economies of scale and the elasticities of substitution of production factors). Primary data was collected from a representative random sample of 98 rural properties. Stochastic production, cost and profit frontier models were used, assuming the Cobb-Douglas and the translog functional forms. In order to identify the factors determining the efficiency differentials, the single-stage stochastic model proposed by Battese and Coelli (1995) was adopted, and a set of hypotheses were tested, based on different standpoints of economic theory (NEI, ECT, theories of human capital, theories of production management, etc) as well as on the characteristics of citrus production. The results of the study showed the existence of technical inefficiency (28.4% on average), as well as inefficiency of cost (30.6% on average), and of profits (55.3 on average) among the farms. The translog production and cost frontiers indicated the existence of an initial zone with strong growing returns/economies of scale which go into exhaustion until decreasing returns begin to occur/diseconomies of scale. The optimum scale, calculated from the parameters estimated in the translog production frontier, showed to be between 70,000-100,000 boxes, while the optimal scale for the translog cost frontier showed to be between 130,000-300,000 boxes. One of the explanations for this difference is the lower prices for fertilizers and labor paid by large farmers, which is a source of pecuniary scale economy. As for the factors determining the differential in technical, cost, and profit efficiency, it was possible to verify a significant effect coming from a set of variables which can be divided into structural (irrigation, greening and land consolidation), managerial (adoption of management tools, use of plural forms of governance, choice of marketing channels, rural production diversification and technical assistance), institutional (occurrence of problems in the contracts of sale, formation of expectations, perception of enforcement in commercial contracts and financial leverage), and human capital (schooling and access to information). Therefore, some of the main research hypotheses were corroborated in the empirical analyses. Lastly, based on the results of the study, a set of suggestions that may subsidize the formulation of public policies and private strategies for the citrus production of São Paulo were made.